Congenital Urethral Anomalies in Boys. Part II - Kajbafzadeh, Abdolmohammad (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: In the second part of this article, congenital urethral anomalies other than posterior urethral valve were reviewed. Materials and Methods:Â The anomalies considered in the current review were anterior urethral valve, lacuna magna, syringocele, Cobb’s collar, duplication of urethra, megalourethra, and prostatic urethral polyps. The literature was extensively reviewed concerning the presentations, diagnosis, different types of treatment modalities, morbidity, mortality, and new concepts for the above disorders. Result: Anterior urethral valves or diverticula are the most prevalent congenital anomalies of anterior urethra. The lacuna magna is the largest depression in the dorsal aspect of the fossa navicularis. It is demonstrable on a well-performed voiding cystourethrography of the distal urethra. The dilated Cowper’s gland duct is the other missed diagnosed anomaly of the urethra in boys. The congenital narrowing of the bulbar urethra with a variable clinical presentation and obstruction grade and different types of anterior urethral obstruction are the most common presentation of these anomalies. However, other symptoms or signs including, hematuria, bloody spotting on underwear, discomfort or sever pain in the vicinity of the glance, interrupted voiding, infection, bulging of anterior urethra, enuresis, and postvoiding dribbling are the only nonspecific manifestations of these disorders. Conclusion: All of these disorders are demonstrable on a well-performed voiding cystourethrography of the distal urethra. The urologist must be aware about these uncommon congenital anomalies and the anterior urethra should be carefully evaluated for such anomalies. Diagnosis of these entities is elusive unless the physician is looking for them. Nonspecific symptoms mentioned here besides radiographic findings can be a valuable clue for diagnosis.